Coercion, compliance, and the collapse of the Soviet command economy - Harrison, Mark (The Economic history review, 2002)
Are command systems that rest on coercion inherently unstable, and did the Soviet economy collapse for this reason? Until it collapsed, the Soviet economy did not appear unstable. Why, then, did it collapse? A game between a dictator and a producer shows that a high level of coercion may yield a stable high-output equilibrium, that stability may rest in part on the dictator's reputation, and that a collapse may be brought about by adverse trends in the dictator's costs and a loss of reputation. The facts of the Soviet case are consistent with a collapse that was triggered by the strike movement of 1989.